The Rudolf Mössbauer story his scientific work and its impact on science and history - Kalvius, Michael. (Springer, 2012)
The “Rudolf Mössbauer Story” recounts the history of the discovery of the “Mössbauer Effect” in 1958 by Rudolf Mössbauer as a graduate student of Heinz Maier-Leibnitz for which he received the Nobel Prize in 1961 when he was 32 years old. The development of numerous applications of the Mössbauer effect in many fields of sciences , such as physics, chemistry, biology and medicine is reviewed by experts who contributed to this wide spread research. In 1978 Mössbauer focused his research interest on a new field “Neutrino Oscillations” and later on the study of the properties of the neutrinos emitted by the sun. How the Mössbauer story started in Munich -- Discovery of the Mössbauer-effect and its early history -- Discovery of the recoil free resonance absorption of Gamma-Rays -- The iridium and early iron age -- Identification of hyperfine interactions in the Mössbauer spectra -- Other important Mössbauer transitions -- CALTECH years of Rudolf Mössbauer -- Selected highlights of Mössbauer spectroscopy -- Determination of the nuclear parameters of many Mössbauer-transitions -- Isomer shifts in solid state chemistry -- Internal fields -- Time-dependent effect -- Medical and biological applications -- Relativistic effects -- Mössbauer effect with synchrotron radiation -- Outlook -- Mössbauer effect with neutrinos -- Dreams with synchrotron radiation -- Neutrino oscillations - The second love of Mössbauer -- The “Second Mössbauer Effect”.